2020
DOI: 10.1111/ecc.13289
|View full text |Cite
|
Sign up to set email alerts
|

Patient ambassador support: Experiences of the mentorship between newly diagnosed patients with acute leukaemia and their patient ambassadors

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Likewise, our qualitative evaluation of PAS showed that patients experienced a feeling of being understood, a cohesive relationship leading to hope and a feeling of being able to cope with their situation. Simultaneously, patient ambassadors experienced a sense of meaningfulness and gratitude for life [15].…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, our qualitative evaluation of PAS showed that patients experienced a feeling of being understood, a cohesive relationship leading to hope and a feeling of being able to cope with their situation. Simultaneously, patient ambassadors experienced a sense of meaningfulness and gratitude for life [15].…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Peer support may benefit not only the person being supported but also the supporter [14,15]. Peers possess an understanding and a first-hand experience of the disease and its treatment, and may provide support to a peer who is at an earlier stage of treatment or recovery [16].…”
Section: Introductionmentioning
confidence: 99%
“…Family caregivers were primarily matched with a caregiver ambassador with a similar diagnosis or life stage, and aligned as closely as possible to their preferences, which may explain the high satisfaction and low dropout rate. Furthermore, studies show that similar age and gender are perceived less important for successful matching [ 34 ], while similar experiences and common interests help build reciprocal, trusting relationships [ 15 , 35 ]. Social comparison processes can explain the benefits of a successful match, suggesting that comparisons aid in interpreting illness encounters, health threats, and disconcerting symptoms [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Social comparison processes can explain the benefits of a successful match, suggesting that comparisons aid in interpreting illness encounters, health threats, and disconcerting symptoms [ 36 , 37 ]. Previous peer support studies in cancer patients highlight that social comparison positively impacts patients’ understanding of their current situation and expectations, as well as reassures newly diagnosed patients [ 14 , 15 ]. However, if experiences are too dissimilar, there is the risk of alienation and poorer perceived support [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation